New antibacterial hydrophobic assay reveals Abies balsamea oleoresin activity against Staphylococcus aureus and MRSA. (24th December 2016) - Coté, Héloïse; Boucher, Marie-Anne; Pichette, André; Roger, Benoit; Legault, Jean
Abstract: Ethnopharmacological relevance: Oleoresin of Abies balsamea (L.) Mill. was used by Native Americans of the boreal forest of Canada and French Canadians to treat various infections, suggesting that oleoresin has antibacterial properties. Aim of the study: In this study, the antibacterial activity of whole oleoresin from A. balsamea was investigated against E. coli, S. aureus and two methicillin-resistant S. aureus (MRSA) strains using a new sensitive assay developed to evaluate hydrophobic matrix and compounds. Materials and methods: Antibacterial activity of oleoresin was first investigated using dilution and disk diffusion methods against E. coli and S. aureus, and compared to a new sensitive assay for hydrophobic matrix. Moreover, whole oleoresin was analyzed by GC–MS to characterize the composition and to identify the compounds responsible of the antibacterial activity. Results: The results showed that whole oleoresin was inactive against Gram-negative E. coli (MIC90 >90 µg/ml) but active against Gram-positive S. aureus and MRSA with MIC90 ranging from 18.2 to 30 µg/ml. The oleoresin is mainly composed of monoterpene (28%), sesquiterpenes (2%), and diterpenes (45%). Resin acids were found, in part, responsible for the antibacterial activity of whole oleoresin. Isopimaric acid and levopimaric acid are the most active with a MIC90 of respectively 9.7 µg/ml and 10 µg/ml. Conclusion: This study supports the use of oleoresin of A. balsamea by the Native Americans and French Canadians to treat bacterial infections due to S. aureus . Graphical abstract: